Changes of the sweet taste sensitivity due to aerobic physical exercise - Ni Luh Putu Ayu Wardhani; Anis Irmawati; Jenny Sunariani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Sweet taste is a pleasant sensation. Sweet taste is mostly consumed and fancied by many people. Physiologically, glucose is body's source of energy, but if over used it can be affected to the body's metabolism. This can be worsen if the person's not doing a healthy lifestyle. One way to implement a healthy lifestyle is by doing physical exercises. Purpose: The aim of this study was to determine changes in sensory sensitivity of sweet taste due to aerobic physical exercise. Methods: This study was conducted on subjects aged 20 to 30 years. The subjects did aerobic exercise using 80% load of MHR. The measurement sensitivity of the senses of the sweet taste was done for three times before the subject take aerobic physical exercise, four weeks after doing aerobic physical exercise, and eight weeks after doing aerobic physical exercise. Results: There was significant difference towards sensitivity of sweet taste sense before doing aerobic physical exercise, 4 week after doing the aerobic physical exercise, and 8 week after doing aerobic physical exercise. Conclusion: Aerobic physical exercise during eight weeks increase sweet taste sensitivity.Latar belakang: Rasa manis memberikan sensasi yang menyenangkan. Rasa manis merupakan jenis rasa yang paling banyak dikonsumsi dan disukai oleh sekelompok orang. Secara fisiologis, glukosa bisa berperan sebagai sumber energi, namun apabila dikonsumsi secara berlebihan dapat menimbulkan efek patologis. Hal ini dihubungkan dengan individu yang mempunyai gaya hidup yang tidak sehat. Salah satu cara yang bisa dilakukan untuk membiasakan gaya hidup sehat adalah dengan latihan fisik (olah raga). Tujuan: Penelitian ini bertujuan untuk membuktikan adanya perubahan sensitivitas indera kecap rasa manis setelah melakukan latihan fisik aerobik. Metode: Penelitian ini melibatkan subyek laki-laki, berusia 20–30 tahun. Subjek melakukan latihan fisik aerobik dengan intensitas sebesar 80% maximal heart rate. Sensitivitas indera kecap rasa manis diukur 3 kali, yaitu sebelum melakukan latihan fisik aerobik, dan 4 serta 8 minggu setelah latihan fisik aerobik. Hasil: Terdapat perbedaan yang signifikan pada sensitivitas indera kecap rasa manis sebelum 4 dan 8 minggu sesudah latihan fisik aerobik. Kesimpulan: Latihan fisik aerobik selama 8 minggu menyebabkan peningkatan sensitivitas indera kecap rasa manis.